All by myself - Mayer, Mercer 1943- (New York Golden Books, 1983)
All the many things a young child can do independently are demonstrated (tying shoes, riding bike, kicking ball), but there is one thing one cannot do alone.
"A Golden look-look book."
Keywords: Children's stories, American; Self-reliance -- Fiction